Reality : a very short introduction - Westerhoff, Jan. (©2011, 2011)
'What is real?' has been one of the key questions of philosophy since its beginning in antiquity. But it is not just a question that philosophers ask. This Very Short Introduction discusses what reality is by looking at a variety of arguments, theories, and thought-experiments from philosophy, physics, and cognitive science.
Includes bibliographical references (p. 111-119) and index.
Keywords: Reality